THE PROBLEM OF MAN AND NATURE IN THE STORY - Qurbonova, Gulbahor (FILOLOGIYA UFQLARI JURNALI, 2024)
Recognized as the "Best Work of the Year" at the time of this article, the story "Abyssal Sky" is a comparative analysis of Chingiz Aitmatov’s "White Ship" through the experiences of children. The works show the tragic end of the problem of man and nature.